Identification of an antibacterial Withanolide (Dinoxin B) from leaf of Datura inoxia Mill. - Chandni Tandon; Priti Mathur; Manodeep Sen; Sanjeev Kanojiya (International Journal of Phytomedicine, 2016)
Natural medicines are gaining popularity due to the alarming incidence of bacterial resistance even in regions with improved healthcare systems. Hence, there is a distinct and constant need for isolating medicinally active compounds from different natural sources. Taking this into consideration, experiment was done in order to isolate and identify an antibacterial compound from Datura inoxia through bioassay and Mass spectroscopy technique. The ethanol, hexane and aqueous leaf extracts of Datura inoxia were screened for